A comprehensive path planning framework for patrolling marine environment. (July 2020) - Zhou, Xiao; Cheng, Liang; Li, Weidong; Zhang, Chuanrong; Zhang, Fangli; Zeng, Fanxuan; Yan, Zhaojin; Ruan, Xiaoguang; Li, Manchun
Abstract: Ship navigation safety is a growing concern in maritime transportation and shipping industry. Rescue ship patrol is an important operation for improving navigation safety in the marine environment. This paper proposes a patrol path support framework, which incorporates multiple criteria decision making, geographical information system (GIS), and linear programming, to determine optimal paths for rescue ships on routine patrols. The proposed framework comprises three steps. First, a navigation risk index is created to estimate the rescue demand by using GIS-based multi-criteria decision analysis. Second, the patrol area of a rescue ship is identified based on a temporal accessibility model. Third, the optimal patrol path is determined by solving a linear programming problem. The northeastern South China Sea was taken as the area for a case study to demonstrate the usefulness of the proposed framework, and the optimum patrol path was identified successfully. The findings of this study may help the concerned authorities to develop maritime patrol path planning.